Pengaruh Experiential Marketing terhadap Experiential Value pada Pengguna Smartphone - Gowinda, Dewa Heri; Suprapti, Wayan Sri (E-Jurnal Manajemen; Vol 3 No 8 (2014), 2014)
Smartphone is a mobile phone that is very popular with consumers . This leads to intense competition in the smartphone industry . Intense competition is forcing companies to innovate and devise strategies to instill positive experiential value . This study aims to determine the effect of experiential marketing indicator that sense experience, feel experience , think experience , act experience , relate experience on experiential value on the smartphone users in the city of Denpasar . Respondents used are 100 people with non-probability sampling method sampling . Engineering analysis is a multiple linear regression analysis . Based on the analysis , it is known that the five indicators of experiential marketing significantly influence the experiential value on the smartphone users in the city of Denpasar
Keywords: Sense experience , experience Feel , Think experience , experience Act , Relate experience , Experiential value , Smartphone Users.